2018
DOI: 10.1016/j.medengphy.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Towards the enhancement of body standing balance recovery by means of a wireless audio-biofeedback system

Abstract: Human maintain their body balance by sensorimotor controls mainly based on information gathered from vision, proprioception and vestibular systems. When there is a lack of information, caused by pathologies, diseases or aging, the subject may fall. In this context, we developed a system to augment information gathering, providing the subject with warning audio-feedback signals related to his/her equilibrium. The system comprises an inertial measurement unit (IMU), a data processing unit, a headphone audio devi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…A total of 53 studies were excluded in full-text screening as follows: WIST studies without feedback ( n = 14) [ 55 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; feedback without an inertial sensor (s) [ 94 ]; sensors integrated into equipment ( n = 5), e.g., seat sensors and robotic devices rather than those worn by an individual [ 95 , 96 , 97 , 98 , 99 ]; standing balance and/or lower body sway ( n = 5) [ 100 , 101 , 102 , 103 , 104 ]; abstracts ( n = 7) [ 105 , 106 , 107 , 108 , 109 , 110 , 111 ]; stroke/other neurological rehabilitation studies ( n = 4) [ 112 , 113 , 114 , 115 ]; a non-work setting ( n = 3) [ 116 , 117 , 118 ]; no evaluation of WIST feedback effectiveness ( n = 6) [ 119 , 120 , 121 , 122 , 123 , 124 ]; research proposal ( n = 1) [ 125 ]; and validity and reliability s...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 53 studies were excluded in full-text screening as follows: WIST studies without feedback ( n = 14) [ 55 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; feedback without an inertial sensor (s) [ 94 ]; sensors integrated into equipment ( n = 5), e.g., seat sensors and robotic devices rather than those worn by an individual [ 95 , 96 , 97 , 98 , 99 ]; standing balance and/or lower body sway ( n = 5) [ 100 , 101 , 102 , 103 , 104 ]; abstracts ( n = 7) [ 105 , 106 , 107 , 108 , 109 , 110 , 111 ]; stroke/other neurological rehabilitation studies ( n = 4) [ 112 , 113 , 114 , 115 ]; a non-work setting ( n = 3) [ 116 , 117 , 118 ]; no evaluation of WIST feedback effectiveness ( n = 6) [ 119 , 120 , 121 , 122 , 123 , 124 ]; research proposal ( n = 1) [ 125 ]; and validity and reliability s...…”
Section: Resultsmentioning
confidence: 99%
“…From a physiological standpoint, it could be speculated that the restoration of efficient sound transmission may partially influence postural function, possibly providing subjects with additional information about the surrounding environment to better control body movements; sound may act as a spatial landmark helping integrating other sensory inputs, thus improving overall balance control. 33,34 In this light, it has been proposed that a sound-induced vestibular activation would evoke a vestibulo-postural reflex, influencing balance; 35,36 indeed, previous works highlighted various effects of sound on posture from increased oscillation on the mediolateral (x) plane 35 to reduced sway in the same axis 37 and beneficial effects on anteroposterior (y) oscillations. 38 In our study population, a reduction in postural sway was found in both x and y planes with eyes open as well as closed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They are able to detect the time instants for the first and the last contacts. Secondly, we performed the motion capture and the motion analysis through the Movit System G1 (Captiks, Rome, Italy), which provides accelerometer, gyroscope, magnetometer, quaternion, barometer synced data and is composed of 10-DOF wireless wearable small inertial devices and an USB wireless receiver (Costantini et al, 2018 ; Ricci et al, 2019a , b ; Saggio, 2020 ).…”
Section: Methodsmentioning
confidence: 99%